(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study examines the legislative framework governing digital media ethics in the Arab world in light of the rapid growth of artificial intelligence, through a comparative analytical approach between the regulations applied in the Kingdom of Saudi Arabia and the Arab Republic of Egypt. The research is grounded in the profound transformations that digital technologies and AI-driven tools have introduced to the media landscape, reshaping content production, dissemination, and audience interaction, and raising complex ethical and legal challenges. The study argues that digital media has moved beyond the control of traditional journalistic institutions, becoming an open and interactive space dominated by algorithms, user-generated content, and AI-generated media. This transformation has intensified ethical concerns related to credibility, transparency, accountability, privacy protection, deepfake technologies, and algorithmic bias. In this context, the research investigates the extent to which existing Arab media legislations are capable of regulating digital media practices without undermining freedom of expression or stifling innovation. Methodologically, the study adopts a descriptive-analytical and comparative approach, analyzing relevant media laws, cybercrime regulations, and digital content governance frameworks in Saudi Arabia and Egypt, alongside a review of contemporary Arab and international literature on digital media ethics and artificial intelligence. The findings reveal a noticeable disparity between the two legislative models: while Saudi regulations demonstrate a relatively higher level of modernization and adaptability to digital transformations, Egyptian legislations remain more inclined toward traditional punitive approaches, with limited integration of ethical and technological dimensions related to AI. The study concludes that, despite recent legislative developments, Arab media regulations still suffer from significant ethical and legal gaps in addressing AI-driven media practices, particularly concerning disclosure of AI-generated content, clarification of legal responsibility, and protection of digital privacy. Accordingly, the research recommends the development of a comprehensive and unified Arab legislative and ethical framework for digital media that balances freedom of expression with professional responsibility, integrates legal regulation with media self-regulation, and reflects the cultural and social specificity of the Arab digital environment in the age of artificial intelligence.